The Influence of Work Involvement and Social Competence on the Performance of State Elementary School Teachers - Suzilawati AN, Suzilawati AN; Gimin, Gimin; Natuna, Daeng Ayub (Journal of Educational Sciences, 2022)
Several problems were found such as the teacher was not sensitive to the problems of students, the teacher was not enthusiastic in teaching, the teacher could not show in front of the students that he mastered the material well, there were still many teachers who could not good use of information technology, and the lack of togetherness among fellow teachers in completing assignments. This study uses a saturated sample technique. The number of samples is the entire population of 55 teachers. The results of this study shows that there is a positive and significant influence between Job Involvement on Social Competence. The higher the work involvement given, the higher the social competence of the teacher. There is a positive and significant influence between the variables of teacher performance on social competence. The higher the level of performance possessed by the teacher, the higher the level of social competence possessed by the teacher. There is also a jointly significant influence between the variables of work involvement and teacher performance on social competence. The higher the work involvement and performance of the teacher, the higher the level of social competence possessed by the teacher with the assumption of permanent work involvement. Furthermore, the higher the level of performance possessed by the teacher, the higher the level of social competence possessed by the teacher with the assumption of permanent work involvement.